Given that x1*x2 = - 3 calculate t if x^2 - 2x +t = 0

giorgiana1976 | Student

Being a quadratic, the equation has 2 roots.

We know, from enunciation that the product of the roots is -3.

We know also, using Viete's relations, that the product of the roots of the quadratic is the ratio: c/a.

We'll identify the coefficients c and a.

c = t


a = 1

So, x1*x2 = c/a

We'll sbstitute the product by the value -3 and the ratio by the identified coefficients.

-3 = t/1

So, t = -3.

The quadratic equation is:

x^2 - 2x -3= 0

phucnguyen08 | Student

x1={-b-[b^2-4ac]^1/2}/2a= {2-(2^2-4*1*t)^1/2}/2*1




x1*x2=-3           {[2-(4-4t)^1/2]*[2+(4-4t)^1/2}*1/4=-3


[4-(4-4t)]*1/4=-3             (4-4+4t)*1/4=-3

(0+4t)*1/4=-3              t=-3

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question